DIDACTIC POSSIBILITIES OF THE CONCEPT OF THE “THIRD TEACHER” IN THE PEDAGOGICAL EDUCATION CLUSTER (European Journal of Pedagogical Initiatives and Educational Practices, 2026)
The article covers the content of the “Third Teacher” project in the pedagogical education cluster and the possibilities of its implementation in practice. The implementation mechanisms of the “Future Teacher” project are discussed. Also, theoretical ideas are put forward regarding the individual education strategy, competency-based and person-oriented approaches.